Effects of perinatal oxycodone exposure on the cardiovascular response to acute stress in male rats at weaning and in young adulthood - Sithisarn, Thitinart; Bada, Henrietta S.; Charnigo, Richard J.; Legan, Sandra J.; Randall, David C. (Frontiers in Physiology, 2013)
Oxycodone (OXY) is one of the most commonly abused opiates during pregnancy. Perinatal opiate exposure (POE) is associated with neurobehavioral and hormone changes. Little is known about the effects of perinatal OXY on the cardiovascular (CV) responses to stress. Objectives: to determine the effects of POE on: (1) CV responses to acute stress and ability to discriminate using a classical conditioning paradigm; (2) changes in CV response to the paradigm and retention of the ability to discriminate from postnatal day (PD) 40 to young adulthood. Methods: Pregnant rats were given i.v. OXY or vehicle (CON) daily. OXY and CON males were fitted with BP telemetry units. Offspring were classically conditioned by following a pulsed tone (CS+) with tail shock. A steady tone (CS-) was not followed by shock. BP and HR were recorded during resting periods and conditioning. Changes in BP, HR from composite analysis were compared. The paradigm was repeated on PD 75. Results: At PD 40, OXY rats had a lower baseline mean BP (OXY: 114.8 ± 1.0 vs CON: 118.3 ± 1.0 mm Hg; mean ± SEM) but larger amplitude of the conditional BP increase during the stress response (OXY +3.9 ± 0.4 vs CON +1.7 ± 0.4 mm Hg.) Both OXY and CON rats were able to discriminate between CS+ and CS-. At PD 75, the effects of OXY on the increased amplitude of the conditional BP had dissipated (CON: +3.4 ± 2.3 vs OXY: +4.5 ± 1.4 mm Hg). BP responses to the stress and non-stress stimuli did not differ in the OXY group, suggesting that OXY may have decreased the ability of the offspring to discriminate (OXY: CS+: 147.1 ± 1.6, CS-: 145.9 ± 1.6 mm Hg vs CON: CS+: 155.4 ± 2.7, CS-: 147.8 ± 2.7 mm Hg). Conclusion: POE is associated with subtle alterations in stress CV responses in weanling rats which dissipate when the conditioning is repeated at an early adult age. Although POE effect on the ability to discriminate at weanling age could not be detected, POE may impair retention of this ability in adulthood.